(untitled) (Andamios, Revista de Investigación Social, 2014)
We have been reading about a stigmatizer and nonhistorical mass media discourse which associates young people to death. This discourse is based on several stories which consider young people as dangerous for the rest of the population and also dangerous for their own lives. In order to give a better opinion to journalists’ work, this present analysis deals with the youth activities in which life is in danger. These activities are not irrational. They are included in a group of socialized young people who live in a time of global uncertainty and regional vulnerability. The second conjecture refers to the relation between risky youth activities and what it is known as damage: the injuries produced by the military dictatorship and by thirty years of nonliberal policies in the region.